Oblicz wartość wyrażenia:
(x² -2x + 1):(x³ -3x² +3x - 1) dla x = ∛2 - 1
Szczegóły:
1. x = ∛2 - 1 - Tylko 2 jest pod pierwiastkiem, bez jedynki.
2. (x² -2x + 1):(x³ -3x² +3x - 1) - kreskę ułamkową zastąpiłam znakiem dzielenia.

Odpowiedź: (-∛4 - 2∛2 - 4):(6)

1

Odpowiedzi

Najlepsza Odpowiedź!
2009-10-24T19:40:29+02:00
(x² -2x + 1):(x³ -3x² +3x - 1) dla x =√ 2 - 1
(x-1)²:((x³-1)-3x(x-1))=
(x-1)²:[(x-1)(x²+x+1)-3x(x-1)]=
(x-1)²:[(x-1)(x²+x+1-3x)]=
(x-1)²:[(x-1)(x²-2x+1)]=
(x-1):(x²-2x+1)=

dla x =√ 2 - 1
(√2-1-1):[(√2-1)²-2(√ 2 - 1 )+1]=
(√2-2):[2-2√2+1-2√2+2+1]=
(√2-2):(6-4√2)=
(√2-2)*(1/(6-4√2)=
(√2-2)*(6-4√2)/[(6)²-(4√2)²]=
(6√2-4*2-12+8√2)/(36-32)=
(14√2-20)/4=
2(7√2-10)/4=(7√2-10)/2